Energy‐Loss Reduction as a Strategy to Improve the Efficiency of Dye‐Sensitized Solar Cells. Issue 10 (27th June 2019) - Yao, Zhaoyang; Guo, Yaxiao; Wang, Linqin; Hao, Yan; Guo, Yu; Franchi, Daniele; Zhang, Fuguo; Kloo, Lars; Sun, Licheng
Abstract : Four weak donor backbones (BT, BTP, BT2, and BT3), featuring stepwise enhanced electron‐donating capacities, are designed and synthesized. The sp 3 type carbons introduced are tethered with auxiliary groups to generate a better electron‐blocking stereoscopic structure. A series of NB dyes are subsequently synthesized from these central cores by end‐capping a strong diphenylamine donor and a planar heterocyclic acceptor 4‐(benzo[ c ][1, 2, 5]thiadiazol‐4‐ylethynyl)benzoic acid. The fine‐tuning of steric configurations and energy levels of the resulting dye molecules reduces the energy losses significantly when applied in dye‐sensitized solar cells. These devices offer one of the highest open‐circuit voltages (≈1.03 V) reported so far, and high power conversion efficiencies of 9.6%–12.1% using the NB dyes in combination with a well‐developed cobalt‐tris(4‐methoxyphenyl)amine‐based tandem electrolyte. Abstract : Four delicately designed dyes are synthesized. The fine‐tuning of energy levels and 3D structures of the dyes greatly reduces the energy losses of dye‐sensitized solar cells (DSSCs). Finally, DSSCs made with the NB6 dye and a cobalt‐tris(4‐methoxyphenyl)amine tandem electrolyte show one of the highest reported open‐circuit voltages of 1.03 V and an impressive power conversion efficiency of ≈12.1%.